Serum ferritin as a risk factor for type 2 diabetes mellitus, regulated by liver transferrin receptor 2. Issue 12 (25th November 2021) - Zhang, Rui; Huang, Xinmei; Li, Yue; Yu, Zhiyan; Wu, Yueyue; Zha, Bingbing; Ding, Heyuan; Zang, Shufei; Liu, Jun
Abstract : Objective: The aim of this study was to evaluate the effect of TFR2 on iron storage in type 2 diabetes. Methods: A cross-sectional study was conducted among 1938 participants from the Jiangchuan Community of Shanghai. A total of 784 participants with T2DM and 1154 normal participants (non-T2DM) were enrolled in this study. Serum ferritin, fasting blood glucose, postprandial blood glucose, and HbA1C (glycated hemoglobin A1c) levels were determined. Eighteen Wistar male rats were randomly assigned into three groups ( n = 6/group): rats in a high-fat diet streptozotocin (HFD+STZ) group were fed with HFD for 4 weeks and intraperitoneally injected with streptozotocin (STZ); rats in a control group were fed with a standard diet for 4 weeks and intraperitoneally injected with buffer; rats in an STZ group were fed with a standard diet for 4 weeks and intraperitoneally injected with streptozotocin. Glucose tolerance test was performed at the end of the study. Blood samples and liver tissues were assessed for liver TFR2, blood glucose, serum ferritin, and iron levels. Results: The mean serum ferritin level of T2DM participants was significantly higher than that of the control group (227 (140–352) vs 203.5 (130.5–312) ng/mL, P < 0.05). Serum ferritin level was an independent risk factor for T2DM (high ferritin group vs low ferritin group, 1.304 (1.03–1.651), P < 0.05). Diabetic rats showed reduced liver TFR2 levels, with increased serum ferritin levels. Conclusion: T2DM participants exhibited iron disorder with elevated serum ferritin levels. Elevated serum ferritin levels in diabetic rats were accompanied by reduced liver TFR2 levels.